ANALYSIS OF THE INDEX OF CORPORAL MASS (IMC); HEART FREQUENCY AND ARTERIAL PRESSURE OF PATIENTS OF BOTH PSYCHOTIC SEXES is NEUROTIC OF THE HOSPITAL FILADÉLFIA OF THE MUNICIPAL DISTRICT OF CANDID MARSHAL OF RONDON - PARANÁ (Fiep Bulletin - online, 2014)
The objective of the present study went analyze and to compare the Index of Corporal Mass, heart frequency and arterial pressure. In the sample, they were selecionados(as) 80 patient of both sexes, being 40 women and 40 men voluntários(as), in the age group understood among 30 to 70 years of age, neurotic and psychotic patients of the Hospital Filadélfia of the municipal district of Marechal Cândido of Rondon - PR.  The used methodology was a field research, with application only of a pré tests. As instrument was used a ribbon antropometrica SANNY, it balances electronic Crystal (capacity of 150 kg). AND for aferir the arterial pressure the esfigmomanômetro was used AND to verify the heart frequency the monitor of POLAR FC it was used F1 TM. In the statistical analysis of the work the " Test " was used t " it goes Students " to have given pareados, together with the obtaining of the averages and standard deviations of the data obtained in the pré-test of the study. A level of significância of p was adopted
Keywords: Patient; psychosis; neurosis; IMC (index of corporal mass); Arterial Pressure; Heart Frequency